Two new species of Anabunda Emeljanov (Hemiptera: Fulgoromorpha: Achilidae) from Australia - Moir, Melinda L.; Fletcher, Murray J. (Zootaxa, 2006)
Two new species of Achilini from eastern Australia are described and keys to the genera of Achilini in Australia, and species of the genus Anabunda, are provided. In addition, the type species of Anabunda is redescribed and the recorded distribution extended. The new species are Anabunda murrayfletcheri sp. nov. from Queensland, and A. minuta sp. nov. from New South Wales and Queensland. Both represent short-range endemic species, possibly under threat because of rapid urbanisation within their ranges. Biogeography and plant associations are discussed briefly.